RANCANG BANGUN SISTEM INFORMASI PENJUALAN ONLINE BERBASIS WEB PADA TOKO ROTI AGUNG BAKERY MENGGUNAKAN METODE SCRUM - Evi Vitriana; Hadi Sucipto; Ginanjar Setyo Permadi; Muhammad Fatkhur Rizal (Inovate, 2025)
Developments in the industrial sector that go hand in hand with technological developments can certainly have a positive impact, one of these positive impacts is improving the economy. The business sector that is currently developing a lot is the business sector that operates in the trade sector. Agung Bakery Bakery is a company that operates in the trading sector by selling various types of bread offline. However, many consumers complain about the lack of online stores available. This shows that there is an opportunity to expand the reach of the business and improve service to customers by introducing an online store. The method used in this research is the Scrum method. The Scrum method was chosen because of its ability to manage projects flexibly and adaptively to changing needs during the development process. The development process begins with identifying user needs, followed by sprint planning, development, testing, and evaluation. Each iteration or sprint results in increased functionality that is tested and validated by users. The aim of this research is to find out the application and workings of a web-based online sales information system using the Scrum method at the Agung Bakery bakery. The result of this research is the application of the Scrum method in developing this system, the results are very targeted and run smoothly. This Agung Bakery bakery website can be used as a solution to the problem being studied. Keywords: Scrum, Website, information system.